Success factors for using ERP systems to improve competitiveness in the hospitality industry. - Serdeira Azevedo, Paula (2014)
ERP (Enterprise Resource Planning) systems emerged as a tool to automate and add efficiency to repetitive business processes, providing managers with a global vision and timely responses to the ongoing business operations, and at the same time solving information fragmentation and disintegration problems. These problems are felt in the hospitality industry just as much as in any other industry. Implementing an ERP system may imply deep modifications in structure, business processes and even the culture of an organization. Despite some drawbacks, the benefit of these kind of IT (Information Technology) systems are numerous and may bring important contributes to increase business competitiveness. In order to achieve the expected benefits there are some critical success factors that have to be closely looked at. The purpose of this paper (supported by a case study of a Portuguese group of companies) is to identify the major success factors when using this kind of systems in the hospitality industry, as well as factors that may obstruct organizations from being competitive. Another goal is to provide some recommendations for organizations of the same type.